Modelling the effect of burning temperature and time on chemical composition of sorghum husk ash for optimum pozzolanic activity (2018)
Sorghum Husk Ash (SHA) can be used as partial replacement for cement in production of concrete due its pozzolanic behavior. This will reduce the cost and environmental pollution associated with the use and production of cement. The aim of this paper is to model the effect of burning temperature and time on chemical composition of SHA for optimum pozzolanic activity. The testing was done at 2-factors, 5-levels using Central composite design of Response Surface Methodology (RSM). Independent variables considered were: burning temperature (500, 600, 700, 800 and 900oC) and time (1, 2, 3, 4 and 5 hours). Dependent variables (chemical constituents) include: Silicon dioxide (SiO ), Aluminum oxide (Al O ), Iron 2 2 3 oxide (Fe O ), Calcium oxide (CaO), Sulphur oxide (SO ), Sodium oxide (Na O), Magnesium oxide (MgO) 2 3 3 2 and Potassium oxide (K O); all determined using atomic absorption spectrophotometer analysis. The 2 results revealed that the ash content decreases as the burning temperature and time increases. Optimum combined percent of SiO , Al O and Fe O (76.047%) which is the criteria for a good pozzolana was 2 2 3 2 3 achieved at temperature of 700oC and time 3 hours.